(untitled) (Journal of Pharma Insights and Research, 2023)
The aim of this study was to formulate and optimize a sublingual tablet of Losartan Potassium, a potent antihypertensive drug. Leveraging the advantages of rapid onset of action and the ability to bypass hepatic metabolism, sublingual tablets provide an effective and convenient approach for hypertension management. The formulation strategy involved the utilization of super disintegrants through the direct compression method. Sublingual drug delivery, known for its systemic advantages, involves administering the drug through the oral mucosa, specifically under the tongue. Preformulation studies involved the characterization of Losartan Potassium using UV, FTIR, and DSC techniques. UV spectroscopy established a quantitative estimation method for the drug, with an absorption maxima at 250 nm. The tablets were then formulated using the direct compression technique. Post-compression studies, encompassing parameters such as weight variation, hardness, friability, wetting time, water absorption, and drug content, were conducted to assess the product’s quality. Sublingual tablets, traditionally employed to enhance the dissolution properties and bioavailability of water-soluble drugs, were developed to facilitate efficient drug absorption without the need for water consumption